Changing Rainfall Pattern in Pokhara Valley, Nepal - Niraula, Nistha; Pokhrel, Baijayanti Mala (The Geographic Base, 2022)
Pokhara valley lies on the southern slope of the Annapurna Range in the Himalayas, Nepal. The mountain range blocks the monsoon originating from the Bay of Bengal in the monsoon season. Based on the observed rainfall data from 1991 to 2021 AD from the Department of Hydrology and Meteorology (DHM), Government of Nepal (GoN), this study aims to assess the monthly, seasonal, and annual pattern of rainfall in Pokhara. Trend analysis for annual rainfall as well as seasonal and monthly rainfall was performed and a regression method was used to find the rate of increase or decrease of the rainfall. Pre- monsoon and monsoon seasons indicate both an upward and a downward trend, whereas post-monsoon and winter seasons illustrates the exact opposite. However, the average monthly rainfall indicates an upward trend, despite the fact that the annual rainfall exhibits both an increasing and a decreasing trend. According to the research, there are rising (+ve) and falling (-ve) trends for the different stations. Although both stations are very near, the precipitation varies broadly. Such massive variation within the short distance might be due to climate change, local wind effects, outflanking of hydraulic structures, and monsoon patterns.